La vía cronológica - Marfull Pujadas, Andreu (La Tempestad, 2020)
https://www.amazon.es/v%C3%ADa-cronol%C3%B3gica-Cronolog%C3%ADa-Fomenko-Nosovskiy/dp/8412176812/ref=sr_1_1?__mk_es_ES=%C3%85M%C3%85%C5%BD%C3%95%C3%91&dchild=1&keywords=la